PENERAPAN ARSITEKTUR TRADISONAL JAWA PADA PERANCANGAN HOTEL RESORT DI KAWASAN PANTAI DRINI KABUPATEN GUNUNG KIDUL YOGYAKARTA - Riza Aji Permana; Tri Endangsih; Anggraeni Dyah S (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
This case study is how to see the application of traditional Javanese architecture in the design of hotels and resorts in the Drini beach area, Gunung Kidul Regency, Yogyakarta. This research focuses on observing several hotels and resorts in the Gunung Kidul Regency area of ​​Yogyakarta in order to get an idea related to the design of hotels and resorts. From the results of observations of several hotel and resort objects, it can be concluded that almost all buildings use a typical Javanese traditional roof, namely the joglo roof or the pyramid roof. Traditional Javanese building wall materials use a lot of bamboo which is woven or wood and are grouped into closed buildings, and in this resort building the use of a roof truss design with a high ridge and roofing materials from natural materials is one of the things that makes Joglo's house feel cold and cool. . The distance at this resort is very good because the distance between buildings will create and bring air circulation in the environment naturally so that it will cause cool air and wind, very suitable because in the design of this resort using a compound type of building. The opening in question is in the form of a hole that is able to bring in winds for fresh air circulation and wind, which is not directly exposed to the path of the sun.